Paradoxes of Doctoral Studies in Education Sciences in the Czech Republic - Dopita, Miroslav; Poláchová Vašťatková, Jana (Qualitative Sociology Review, 2021)
Adequate staffing of university studies with qualified academics was completed thanks to the reimplementation of three-stage university education during the post-socialist restoration of higher education in the Czech Republic. Thus, the doctoral degree of education has been attained by more than four-fifths of academic staff, with over two-fifths of them being aged 50+. The current course of university studies, including doctoral study programs, is influenced by their focus on educational and research strategy. With regards to the regulations for graduating in doctoral studies, doctoral candidates act as homo oeconomicus following neo-liberal educational policy. The conditions for doctoral studies, namely, those in educational sciences, thus lead to paradoxes caused by the current higher educational policy. The objective of the paper is to analyze the neoliberal set-up of the higher education policy of the Czech Republic in the field of doctoral studies in educational sciences in particular and its possible impacts in the area of labor-market integration of graduates and university training of academics.